2020
DOI: 10.3390/en13061322
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Modeling Climate Impacts on Photosynthetic Dynamics with FLUXNET Data and Neural Networks

Abstract: Global warming, which largely results from excessive carbon emission, has become an increasingly heated international issue due to its ever-detereorating trend and the profound consequences. Plants sequester a large amount of atmospheric CO 2 via photosynthesis, thus greatly mediating global warming. In this study, we aim to model the temporal dynamics of photosynthesis for two different vegetation types to further understand the controlling factors of photosynthesis machinery. We experimented with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This approach yielded substantial validation accuracy, as indicated by an R-squared value of 0.75. In studies where different models were used to predict the global GPP, researchers found that the LSTM model consistently had the lowest RMSE [23]. Chen [24] used an LSTM model with temperature and precipitation data as input variables to predict future changes in vegetation NDVI.…”
Section: Introductionmentioning
confidence: 99%
“…This approach yielded substantial validation accuracy, as indicated by an R-squared value of 0.75. In studies where different models were used to predict the global GPP, researchers found that the LSTM model consistently had the lowest RMSE [23]. Chen [24] used an LSTM model with temperature and precipitation data as input variables to predict future changes in vegetation NDVI.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], a Deep Neural Network (DNN) model of the temporal dynamics of plant photosynthesis related to the gross primary product is established for two types of vegetations. Three architectures of DNN models are designed in the study, respectively.…”
Section: Introductionmentioning
confidence: 99%